2018
DOI: 10.1038/mi.2017.110
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Molecular and cellular signatures underlying superior immunity against Bordetella pertussis upon pulmonary vaccination

Abstract: Correction to: Mucosal Immunology advance online publication, 20 September 2017; doi: 10.1038/mi.2017.81 This article was originally published under NPG’s License to Publish, but has now been made available under a CC BY 4.0 license. The PDF and HTML versions of the paper have been modified accordingly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…or i.n. a Mice Decreased bacterial colonization in the lungs [34] OMVs OMV components s.c. Mice Decrease bacterial colonization in the lungs; slightly faster than that of wPV OMVs OMV components PM a or s.c. Mice Decreased bacterial colonization in the lungs, trachea, and nose [35] OMVs deriving from B. parapertussis OMV components i.p. Mice Cross-protection [36] Lipid A-modified OMVs OMV components i.n.…”
Section: Bacterial Infectious Diseases and Advanced Delivery Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…or i.n. a Mice Decreased bacterial colonization in the lungs [34] OMVs OMV components s.c. Mice Decrease bacterial colonization in the lungs; slightly faster than that of wPV OMVs OMV components PM a or s.c. Mice Decreased bacterial colonization in the lungs, trachea, and nose [35] OMVs deriving from B. parapertussis OMV components i.p. Mice Cross-protection [36] Lipid A-modified OMVs OMV components i.n.…”
Section: Bacterial Infectious Diseases and Advanced Delivery Systemsmentioning
confidence: 99%
“…Among them, OMVs have been most thoroughly studied. Many studies have demonstrated that OMVs derived from B. pertussis can protect mice from intranasal pertussis challenge through different immune routes, including intraperitoneal, subcutaneous, intranasal, and pulmonary (PM) [34] , [35] , [76] . The classical administration route of OMVs is subcutaneous or intraperitoneal, which does not cause an IgA reaction [77] .…”
Section: Bacterial Infectious Diseases and Advanced Delivery Systemsmentioning
confidence: 99%
“…Pulmonary vaccination with OMV using a microspray aerosolizer has also been evaluated and was found to lead to improved protection over subcutaneous immunization ( 41 ). It induced mucosal IgA and Th17-type responses, as well as systemic IgG, memory B cells and Th17 cells, while only systemic responses were induced by subcutaneous administration of the OMV.…”
Section: Resultsmentioning
confidence: 99%
“…route for the generation of B. pertussis -specific T RM cells (Allen et al, 2018). Furthermore, studies with B. pertussis OMV have demonstrated that pulmonary immunization is more effective than the s.c. route of immunization for induction of CD103 + T RM cells (Raeven et al, 2018). Therefore, a “prime and pull” strategy of systemic priming followed by nasal boosting might be an interesting approach for induction of systemic and local memory immune response against B. pertussis (Shin and Iwasaki, 2012).…”
Section: Discussionmentioning
confidence: 99%